Electronic and Optical Properties of Rare Earth Atoms Doped Niobium Dichalcogenides NbX₂ (X=S, Se) Monolayers: A First Principle Study (Lafia Journal of Scientific and Industrial Research, 2025)
A First-principles calculation has been carried out to study the electronic, and optical properties of RE (La and Sm) atoms doped monolayer NbX2 (X=S, Se). The properties are studied through the use of density functional theory (DFT) with Perdew–Burke–Ernzerhof-generalized gradient approximation (PBE-GGA) as exchange correlation functional and Time dependent density functional theory (TDDFT) as implementation in Quantum ESPRESSO code. The electronic band structures, as well as density of states (DOS) of these structures, show both are metallic in nature. The analysis of optical properties reveals that both La and Sm doped NbX2 (X= S, Se) Monolayer possess maximum absorptivity in the UV range of incident photon’s energy with minimum energy loss and decrease in reflectivity. Our complete study about the considered compounds describes them as potential candidates for technological applications in plasmonic and optoelectronic devices.